Implementing customer relationship management and service quality in supporting ICT services for CICT, UTM - Abdul Wahab, Nur Ilham (2005)
Good customer relationships are the heart of organizational success. The world today has come to recognized that positive relationships with customers are crucial to an organization’s long-term success. ICT service organizations are no exception. These organizations face greater challenge as they must sustain good relationship with customers and ensure quality services are provided. Realizing this factor, this study is set out to support CICT, UTM through the development of a standard framework for implementing CRM and Service Quality, and an IT-based solution. The project goes through four major phases which includes Strategy, Requirements, Design, and Development. These phases are further enhanced into an operational framework with consists of: (1) Phase1- Strategy, (2) Phase2 – Requirements, (3) Phase3 – Develop CRSQ Framework, and (4) Phase4 - Develop CICT Portal. A top-down approach is used to identify objectives, priorities and high level business needs of CICT. In the requirement phase, qualitative and quantitative data collection methods are used to study the information, process, technology and people involved. Internal interview was carried out with CICT top management and a customer survey was conducted to understand the customers’ expectations and what is important to them. In Phase 3, the input obtained is analyzed into three categories which are the organizational, CRSQ framework and portal analyses. Based on these analyses and theories, components for the framework and portal are identified. For Phase 4, prototyping of the portal commenced with a hybrid of horizontal and vertical prototypes. Contents structure, a site map, a use case diagram and sequence diagrams were designed as a preliminary approach to the prototyping. As a proof of concept, the framework goes through verification and the prototype portal goes through User Acceptance Test to measure users’ acceptance. The result shows that the portal can indeed help CICT in developing good customer relationship and provide quality services.